Liquidity, Profitability, Firm Size, and Financial Distress - Rahmah, Tarissa Aqilla; Akbar, Fajar Syaiful (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This issue arose from the sector's declining performance, with 46 companies on the watchlist board due to consecutive losses and negative earnings growth, indicating potential financial distress. Exacerbated by global economic slowdown and inflationary pressures, this condition was analyzed using quantitative methods. Financial distress was assessed via the modified Altman Z"-Score, with liquidity, profitability, and firm size as independent variables. Thirty-nine companies were selected through purposive sampling, resulting in 117 observations. Employing descriptive statistics, classical assumption tests, and multiple linear regression, this analysis examines the repercussion of these variables on financial distress. The findings show that liquidity, profitability, and firm size jointly generate a considerable impact. Partially, liquidity and firm size negatively relate to financial distress, while profitability shows a positive association. The results yield strategic insights for management and investors in mitigating potential financial distress.